Inflammation of BCG Inoculation Site Scar after the First Dose of an Anti-SARS-CoV-2 mRNA Vaccine - Barros Rodrigues, João (2022)
Inflammatory reactions in the Bacillus Calmette-Guérin (BCG) inoculation scar site have been previously described, in association with viral infections. The inflammation of the scar in association with other vaccines has been described with the flu vaccine and, more recently, after the second dose of mRNA anti-SARS-CoV-2 vaccines (mRNA-1273 e BNT162b2), in two healthcare workers. We present the case of a 27-year-old female, without a relevant past medical history, including no previous SARS-CoV-2 infection, and with inflammation of the BCG scar eight days after the first dose of the mRNA anti-SARS-CoV-2 vaccine. Pharmacovigilance and the notification of adverse events should be encouraged, as a way of warding off hesitation in this process.